Preparation method of coal-based yellow fluorescent carbon dot aqueous solution
The pretreatment of lignite by hydrocavitation combined with specific oxidizing agents was prepared to produce coal-based carbon dots with yellow fluorescence, which solved the problem of single fluorescence color of carbon dots in the prior art and achieved a rich multicolor effect.
Patent Information
- Application Number
- CN202411457517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing coal-based carbon dot preparation methods mainly rely on chemical oxidation, resulting in a decrease in the surface groups of the carbon dots, and the fluorescent color is mainly blue, making it difficult to enrich the color.
The lignite was pretreated by hydrocatalysis combined with a mixed reagent of hydrogen peroxide and peracetic acid, and peeled off to form coal-based carbon dots with yellow fluorescence.
The coal-based carbon dots prepared by this method have yellow fluorescence, enriching the color performance of the carbon dots. Due to the small damage to the surface groups by the physical peeling process, more groups are retained, enhancing the properties of the carbon dots.
Smart Images

Figure CN119461338A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorescent carbon dots, and in particular to a method for preparing a coal-based yellow fluorescent carbon dot aqueous solution. Background Art
[0002] Carbon dots are spherical carbonaceous particles with a size less than 10nm, and the main structure is carbon core + surface group. They have excellent biocompatibility and photoelectric properties, and therefore show great application potential in energy storage, photo / electrocatalysis, bio-labeling, etc. However, the realization of their potential is mainly limited by large-scale preparation. Using abundant coal as raw material and selecting existing industrial methods based on its structural characteristics will be a realistic and reasonable preparation strategy.
[0003] Research shows that the main body of the coal molecular structure is a highly cross-linked amorphous macromolecular polymer in three-dimensional space, and each macromolecule is composed of many basic structural units with similar structures. Although scholars have proposed different molecular structure models, they can be summarized as condensed aromatic layers with side chains. Different layers are interconnected, polymerized, and superimposed into aromatic cores by hydrogen bonds, van der Waals forces, or covalent bonds. The carbon nanocrystals composed of such aromatic cores have many similar structural characteristics to the carbon cores of carbon dots. The dangling bonds, residual (S, N) heteroatoms, and other organic molecules in coal formed after the side chains are broken during the stripping process are excellent donors for the formation of carbon dot surface groups. Therefore, coal is a natural raw material for the preparation of carbon dots.
[0004] At present, the common preparation method of coal-based carbon dots is to use chemical oxidation (mainly strong acid) to break the side chains between carbon nanocrystals, thereby releasing the crystallites to become carbon dots. In addition, the prepared coal-based carbon dots generally emit blue fluorescence under light excitation conditions, as shown in the drawings of the present application specification. Figure 1 For example, Ye et al. [1] The first to use strong acid to oxidize coal to prepare carbon dots, the resulting carbon dots emit blue fluorescence; Saikia et al. [2-4] The carbon dots were prepared by strong acid oxidation and stripping of coals with different metamorphic degrees, and their properties and related applications were studied. The obtained carbon dots also showed blue fluorescence; Kundu et al. [5] Similar studies were also conducted using Indian bituminous coal and anthracite as raw materials, and carbon dots emitting blue fluorescence were also obtained. Dong et al. [6] It was also confirmed that the fluorescence of coal-based carbon dots obtained by acid oxidation was blue. Boruah and Cheng et al. [7,8] Using H2O2 as the main oxidant, coal-based carbon dots with blue fluorescence were also prepared by stripping; in addition, there are other carbon dots prepared directly from various coals with blue fluorescence. [9-12]In the process of preparing coal-based carbon dots by chemical oxidation stripping, the oxidant will also indiscriminately remove the surface groups and dangling bonds of the carbon dots, and the number of surface groups of the obtained carbon dots is small. In this case, the fluorescence mostly comes from the quantum size effect determined by the carbon core, so it is blue.
[0005] The cavitation phenomenon refers to the whole process of the generation, collapse and collapse of cavitation bubbles (cavitation bubbles) in a liquid. At the moment of cavitation collapse, phase change energy is released in various ways such as shock waves, microjets and local hot spots. This process significantly enhances the physical and chemical processes in the liquid, and therefore has been industrially applied to the food, beverage, and pharmaceutical industries. In addition, scholars have also found that the use of cavitation collapse to produce a variety of effects can effectively strip out two-dimensional nanomaterials. Using cavitation to strip coal can cut off the side chains between coal crystallites, releasing them to form carbon dots. Moreover, the stripping process is mainly physical, with little damage to chemical bonds. It can retain the groups and dangling bonds on the surface of the obtained carbon dots to the maximum extent, thereby enriching the properties of the carbon dots. However, to date, there are few reports on the use of cavitation to strip zero-dimensional nanomaterials, and there are no reports on the use of this method to prepare yellow fluorescent carbon dots.
[0006] [1]Ye R.,Xiang C.,Lin J.,et al.Coal as an abundant source of graphenequantum dots[J].Nature Communications,2013,4:2943.
[0007] [2] Saikia M., Das T., Saikia BKA novel rapid synthesis of highlystable silver nanoparticle / carbon quantum dot nanocomposites derived from low-grade coal feedstock[J]. New Journal of Chemistry, 2021, 46: 309-321.
[0008] [3]Saikia M.,Hower JC,Das T.,et al.Feasibility study ofpreparationof carbon quantum dots from Pennsylvania anthracite and Kentucky bituminouscoals[J].Fuel,2019,243:433-440.
[0009] [4]Saikia M.,Singh A.,Dihingia A.,et al.Scalable production celltoxicity assessment and plant growth promotion activities of carbon quantumdots derived from low-quality coal feedstock[J].Chemical Engineering Journal,2022,433:133633.
[0010] [5]Kundu A.,Maity B.,Basu S.Coal-derived graphene quantum dots with aMn2+ / Mn7+nanosensor for selective detection of glutathione by a fluorescenceswitch-off-on assay[J].New Journal ofChemistry,2022,46:7545-7556.
[0011] [6]Dong Y.,Lin J.,Chen Y.,et al.Graphene quantum dots graphene oxidecarbon quantum dots and graphite nanocrystals in coals[J].Nanoscale,2014,6:7410-7415.
[0012] [7]Boruah A.,Bora S.,Thakur A.,et al.Solid-State Phosphors from Coal-Derived Carbon Quantum Dots[J].Acs Omega,2023,8:25410-25423.
[0013] [8]Cheng Z.f.,Wu X.y.,Liu L.,et al.A highly efficient rapid roomtemperature synthesis method for coal-based water-soluble fluorescent carbondots and its use in Fe3+ion detection[J].New Carbon Materials,2023,38:1104-1112.
[0014] [9]Hu Q.,Yang X.,Qi Y.,et al.Optimization of perovskite / carboninterface performance using N-doped coal-based graphene quantum dots and itsmechanism analysis[J].Journal of Energy Chemistry,2023,79:242-252.
[0015]
[10] Hu Q.,Zhao K.,Liu M.,et al.A dual passivation strategy based onF / N co-doped coal-based graphene quantum dots for high-efficiency carbon-based perovskite solar cells[J].Journal of Materials ChemistryA,2024,12:5980-5989.
[0016]
[11] Li M.,Yu C.,Hu C.,et al.Solvothermal conversion of coal intonitrogen-doped carbon dots with singlet oxygen generation and high quantumyield[J].Chemical Engineering Journal,2017,320:570-575.
[0017]
[12] Zhang Y., Li K., Ren S., et al. Coal-Derived Graphene Quantum DotsProduced by Ultrasonic Physical Tailoring and Their Capacity for Cu(II)Detection[J]. Acs Sustainable Chemistry&Engineering, 2019,7:9793-9799. Summary of the invention
[0018] Technical issues solved:
[0019] At present, the preparation method of coal-based carbon dots is mainly based on chemical oxidation. The oxidant used can not only break the cross-linked side chains between carbon nanocrystals, but also indiscriminately oxidize and remove the surface groups of carbon microcrystals in coal. Therefore, the surface groups of the prepared carbon dots are few, resulting in their fluorescence being mainly blue light emitted by the carbon core. The present invention provides a preparation method of coal-based carbon dots with yellow fluorescence: based on the structure and component characteristics of lignite, a mixed reagent of hydrogen peroxide and peracetic acid in a fixed ratio is developed and used as a pretreatment solution for lignite, and then the coal sample is stripped by hydraulic cavitation to prepare coal-based carbon dots with yellow fluorescence. This method provides new ideas and methods for enriching the color of coal-based carbon dots.
[0020] Technical solution:
[0021] To achieve the above objectives, this application is implemented through the following technical solutions:
[0022] A method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, comprising the following specific steps:
[0023] Step 1: Dry the lignite to constant weight, grind it and pass it through a 100-500 mesh sieve to obtain a primary coal sample, and weigh 1-200g of the primary coal sample;
[0024] Step 2: Add the weighed initial coal sample into a mixed solution of 30% peracetic acid and 30% hydrogen peroxide at a mass ratio of 1:1-1:100, stir at 1500r / min for 8h, and filter using a microporous filter membrane to obtain the pretreated coal sample;
[0025] Step 3: Mix the coal sample with water and stir at 1500r / min for 8h to obtain a lignite mixture with a concentration of 1-200g / L;
[0026] Step 4: Transfer the lignite mixture into the cavitation device, start the cavitation program, and adjust and maintain the flow rate at 200L / h-1L / h;
[0027] Step 5: Collect the circulating liquid in the cavitation device, and use a microporous filter membrane to remove the remaining large particles to obtain an aqueous solution of coal-based carbon dots.
[0028] Furthermore, after grinding in the first step, the product is sieved through a 200-500 mesh sieve.
[0029] Furthermore, in the first step, 50-100 g of the initial coal sample is weighed.
[0030] Furthermore, in the second step, the mass ratio of the initial coal sample, the mixed solution of 30% peracetic acid and 30% hydrogen peroxide is 1:20-1:25.
[0031] Furthermore, in the second step, the volume ratio of peracetic acid to hydrogen peroxide in the mixed solution of 30% peracetic acid and 30% hydrogen peroxide is 100:1-1:1.
[0032] Furthermore, in the second step, the volume ratio of 30% peracetic acid to 30% hydrogen peroxide is 10:1-2:1.
[0033] Furthermore, the filtration in the second step and the fifth step is specifically carried out by filtering using a microporous filter membrane with a pore size of 0.1-0.6 μm.
[0034] Furthermore, the concentration of the lignite solution in the third step is 5-50 g / L.
[0035] Furthermore, in the fourth step, the flow rate in the cavitation device is 25L / h-75L / h.
[0036] Furthermore, the cavitation stripping time in the fourth step is 8 hours.
[0037] Principle explanation: When the lignite mixture flows through the cavitation device, the cross section is reduced, the flow rate increases, and the pressure decreases, resulting in cavitation. When the local pressure is lower than the saturated vapor pressure, the cavitation nuclei in the water begin to grow and eventually form cavitation bubbles. When the pressure returns to the saturated vapor pressure area, the cavitation bubbles begin to collapse. In this process, due to the inertial growth of the cavitation nuclei and the compression after the cavitation bubbles are formed, a huge phase change energy of 1-10 is accumulated when they collapse. 18 kW / m 3 It is released in the form of shock wave propagation speed of 2000m / s, microjet high pressure of 450MPa and high shear force of 3.5kPa, thermal action to produce local hot spots of 2000-6000K and chemical action to produce hydroxyl radicals. These actions can effectively cut off the side chains between coal crystallites and release them into the solution to form carbon dots. In addition, after lignite is pretreated with hydrogen peroxide and peracetic acid, new functional groups will be attached to the surface or side chains of the lignite. After cavitation stripping, some of the new functional groups can be retained on the surface of the carbon dots and cause them to produce yellow fluorescence.
[0038] Beneficial effects:
[0039] The present application provides a method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, which has the following beneficial effects:
[0040] 1. The present invention proposes a method for preparing coal-based yellow fluorescent carbon dots, which provides a new method and idea for enriching the polychromaticity of coal-based carbon dots;
[0041] 2. The present invention adopts the hydraulic cavitation method to peel coal samples to prepare carbon dots with yellow fluorescence, which is low in cost, green and environmentally friendly, and requires simple equipment;
[0042] 3. Cavitation has been applied in industrial production on a large scale and has the potential for industrialization;
[0043] 4. At present, the main preparation strategy of coal-based carbon dots is acid oxidation etching. Due to the use of a large amount of strong acid, the production cost increases, the environmental burden increases, and the safety risk increases;
[0044] 5. Strong acid will also indiscriminately oxidize and remove the functional groups and dangling bonds on the surface of coal, which reduces the number of surface groups in the preparation of carbon dots. As a result, the fluorescence of existing coal-based carbon dots mostly comes from the carbon core and is blue. The present invention uses hydrodynamic cavitation to strip lignite to prepare carbon dots, which has the potential of being green, environmentally friendly, low-cost, and scalable production.
[0045] 6. After the coal samples were pretreated with a specific oxidant combination of hydrogen peroxide + peracetic acid, the coal-based carbon dots obtained after stripping would emit yellow fluorescence; this not only provides new ideas and methods for enriching the fluorescence color of coal-based carbon dots, but also shows that this method is less destructive to the surface groups of carbon dots during the preparation process, and some groups can be retained on the surface of carbon dots, providing a new way to use surface groups to adjust the fluorescence color of carbon dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Fluorescence photos of coal-based carbon dots prepared by various methods in references [1]-
[12] under ultraviolet light;
[0047] Figure 2 The fluorescence curve of carbon dots under 390nm light excitation obtained in Example 1 of the present application, wherein the inset is a fluorescence photograph of the carbon dot solution under ultraviolet light;
[0048] Figure 3 The fluorescence emission spectrum of carbon dots under 520nm light excitation and the corresponding excitation spectrum at 590nm were obtained in Example 1 of the present application. DETAILED DESCRIPTION
[0049] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings in the specification.
[0050] Embodiment 1:
[0051] A method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, comprising the following specific steps:
[0052] Step 1: Dry 30g lignite to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample, and weigh 20g of the primary coal sample;
[0053] Step 2: At room temperature, 20 g of the initial coal sample was added to a mixed solution of 30% peracetic acid and 30% hydrogen peroxide (30% is its mass fraction) at a mass ratio of 1:25, and the volume ratio of peracetic acid to hydrogen peroxide was 2:1. After stirring at 1500 r / min for 8 hours, the mixture was filtered using a microporous filter membrane with a pore size of 0.45 μm to obtain a coal sample after cavitation stripping;
[0054] Step 3: Mix the coal sample with 2L of deionized water and stir at 1500r / min for 8h to obtain a lignite mixture;
[0055] Step 4: Place the lignite mixture into the cavitation device, start the cavitation program, adjust and maintain the flow rate at 45L / h, and perform cavitation stripping for 8h;
[0056] Step 5: After the stripping is completed, the circulating liquid in the cavitation device is collected and filtered through a microporous filter membrane with a pore size of 0.45 μm to remove the remaining large particles, thereby obtaining an aqueous solution of coal-based carbon dots.
[0057] Figure 2 The fluorescence curve of the carbon dot solution prepared in Example 1 of the present application under 390nm light excitation, wherein the inset is a fluorescence photograph of the carbon dot solution under 395nm ultraviolet light;
[0058] Figure 3 The fluorescence emission spectrum of carbon dots under 520nm light excitation and the corresponding excitation spectrum at 590nm were obtained in Example 1 of the present application.
[0059] Embodiment 2:
[0060] A method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, comprising the following specific steps:
[0061] Step 1: Dry 30g lignite to constant weight, grind it and pass it through a 400-mesh sieve to obtain a primary coal sample, and weigh 30g of the primary coal sample;
[0062] Step 2: At room temperature, 30 g of the initial coal sample was added to a mixed solution of 30% peracetic acid and 30% hydrogen peroxide (30% is its mass fraction) at a mass ratio of 1:25, and the volume ratio of peracetic acid to hydrogen peroxide was 2:1. After stirring at 1500 r / min for 8 hours, the mixture was filtered using a microporous filter membrane with a pore size of 0.45 μm to obtain 26 g of the coal sample after cavitation stripping;
[0063] Step 3: Mix 26 g of coal sample with 2 L of deionized water and stir at 1500 r / min for 8 h to obtain a lignite mixture;
[0064] Step 4: Place the lignite mixture into the cavitation device, start the cavitation program, adjust and maintain the flow rate at 45L / h, and perform cavitation stripping for 8h;
[0065] Step 5: After the stripping is completed, the circulating liquid in the cavitation device is collected and filtered through a microporous filter membrane with a pore size of 0.45 μm to remove the remaining large particles, thereby obtaining an aqueous solution of coal-based carbon dots.
[0066] Embodiment 3:
[0067] A method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, comprising the following specific steps:
[0068] Step 1: Dry 30g lignite to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample, and weigh 20g of the primary coal sample;
[0069] Step 2: At room temperature, 20 g of the initial coal sample was added to a mixed solution of 30% peracetic acid and 30% hydrogen peroxide (30% is its mass fraction) at a mass ratio of 1:25, and the volume ratio of peracetic acid to hydrogen peroxide was 5:1. After stirring at 1500 r / min for 8 hours, the mixture was filtered using a microporous filter membrane with a pore size of 0.45 μm to obtain 15 g of the coal sample after cavitation stripping;
[0070] Step 3: Mix 15 g of coal sample with 2 L of deionized water and stir at 1500 r / min for 8 h to obtain a lignite mixture;
[0071] Step 4: Place the lignite mixture into the cavitation device, start the cavitation program, adjust and maintain the flow rate at 45L / h, and perform cavitation stripping for 8h;
[0072] Step 5: After the stripping is completed, the circulating liquid in the cavitation device is collected and filtered through a microporous filter membrane with a pore size of 0.45 μm to remove the remaining large particles, thereby obtaining an aqueous solution of coal-based carbon dots.
[0073] Embodiment 4:
[0074] A method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, comprising the following specific steps:
[0075] Step 1: Dry 30g lignite to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample, and weigh 20g of the primary coal sample;
[0076] Step 2: At room temperature, 20 g of the initial coal sample was added to a mixed solution of 30% peracetic acid and 30% hydrogen peroxide (30% is its mass fraction) at a mass ratio of 1:25, and the volume ratio of peracetic acid to hydrogen peroxide was 2:1. After stirring at 1500 r / min for 8 hours, the mixture was filtered using a microporous filter membrane with a pore size of 0.45 μm to obtain 15 g of the coal sample after cavitation stripping;
[0077] Step 3: Mix 15 g of coal sample with 2 L of deionized water and stir at 1500 r / min for 8 h to obtain a lignite mixture;
[0078] Step 4: Place the lignite mixture into the cavitation device, start the cavitation program, adjust and maintain the flow rate at 75L / h, and perform cavitation stripping for 8h;
[0079] Step 5: After the stripping is completed, the circulating liquid in the cavitation device is collected and filtered through a microporous filter membrane with a pore size of 0.45 μm to remove the remaining large particles, thereby obtaining an aqueous solution of coal-based carbon dots.
[0080] The fluorescence of the carbon dots prepared in Example 2, Example 3 and Example 4 is similar to that in Example 1.
[0081] The embodiments proposed in the present invention are embodiments under preferred conditions, but are not limited to the above-mentioned contents. Relevant technicians in this field can easily repeat the above-mentioned embodiments, and further extend and change the scheme, but as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a coal-based yellow fluorescent carbon dot aqueous solution, characterized in that: The specific steps are: Step 1: Dry the lignite to constant weight, grind it and pass it through a 100-500 mesh sieve to obtain a primary coal sample, and weigh 1-200g of the primary coal sample; Step 2: Add the weighed initial coal sample into a mixed solution of 30% peracetic acid and 30% hydrogen peroxide at a mass ratio of 1:1-1:100, stir at 1500r / min for 8h, and filter using a microporous filter membrane to obtain the pretreated coal sample; Step 3: Mix the coal sample with water and stir at 1500r / min for 8h to obtain a lignite mixture with a concentration of 1-200g / L; Step 4: Transfer the lignite mixture into the cavitation device, start the cavitation program, and adjust and maintain the flow rate at 200L / h-1L / h; Step 5: Collect the circulating liquid in the cavitation device, and use a microporous filter membrane to remove the remaining large particles to obtain an aqueous solution of coal-based carbon dots.
2. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: After grinding in the first step, the powder is passed through a 200-500 mesh sieve.
3. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: In the first step, 50-100 g of the initial coal sample is weighed.
4. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: In the second step, the mass ratio of the initial coal sample, the mixed solution of 30% peracetic acid and 30% hydrogen peroxide is 1:20-1:
25.
5. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: In the second step, the volume ratio of peracetic acid to hydrogen peroxide in the mixed solution of 30% peracetic acid and 30% hydrogen peroxide is 100:1-1:
1.
6. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 5, characterized in that: In the second step, the volume ratio of 30% peracetic acid to 30% hydrogen peroxide is 10:1-2:
1.
7. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: The filtration in the second step and the fifth step is specifically performed by filtering using a microporous filter membrane with a pore size of 0.1-0.6 μm.
8. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: The concentration of the lignite solution in the third step is 5-50 g / L.
9. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: The flow rate in the cavitation device in the fourth step is 25L / h-75L / h.
10. The method for preparing a coal-based yellow fluorescent carbon dot aqueous solution according to claim 1, characterized in that: The cavitation stripping time in the fourth step is 8 hours.
Citation Information
Cited By
Preparation method of sodium-doped coal-based yellow fluorescent carbon dots
CN120865891A
Preparation method of coal-based red fluorescent carbon dots
CN120888295A
Preparation method of coal-based red fluorescent carbon dots
CN120888295B